Characteristics of Stroke Infarction Patients At Waled Regional General Hospital, Cirebon Regency 2023 - Wildan Ainunnafis Ahmad; Muhammad Amar Latief; Nurbaiti Nurbaiti (International Journal of Health and Pharmaceutical (IJHP), 2025)
Stroke is a leading cause of death and disability worldwide, with increasing prevalence in Indonesia driven by social and economic development. This study aims to characterize infarct stroke patients at Waled Regional General Hospital, Cirebon, in 2023. A descriptive quantitative study with a retrospective approach was conducted, utilizing secondary data from medical records and CT-Scan reports of all eligible infarct stroke patients, totaling 51 cases. Data collection involved medical record forms and radiology reports, analyzed univariately using frequency distribution and percentages via statistical software. The results showed that most patients were male (54.90%), elderly (60.78%), and predominantly had subcortical infarct lesions (47.06%). No significant association was found between hypertension and lesion location, while the prevalence of hypertension and diabetes mellitus was low at 7.84% and 9.80%, respectively. The study concludes that the primary characteristics of infarct stroke patients in this region are middle-aged to elderly men with subcortical lesions. These findings provide a foundation for developing community-based preventive and educational programs, especially targeting vulnerable age groups. This research is essential for informing local health strategies and strengthening efforts to control stroke risk factors.